2011
DOI: 10.1002/jssc.201100358
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of sesamol using molecularly imprinted polymers containing magnetic wollastonite

Abstract: The magnetic molecularly imprinted polymers (MMIPs) have been synthesized using piperonal molecules as dummy template and magnetic wollastonite composites as support. The resulting composites were applied to selective recognition of sesamol from aqueous solution. MMIPs were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) analysis, transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), thermogravimetric analysis (TGA), and vibrating sample magnetome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Due to the properties of MMIPs, i.e. specific structure, highly expanded surface area and chemical stability, these particles are used as additives for the synthesis of nanotubes [25,26], wollastonite [27] or attapulgite [28].…”
Section: The Synthesis Of Magnetic Molecularly Imprinted Polymersmentioning
confidence: 99%
“…Due to the properties of MMIPs, i.e. specific structure, highly expanded surface area and chemical stability, these particles are used as additives for the synthesis of nanotubes [25,26], wollastonite [27] or attapulgite [28].…”
Section: The Synthesis Of Magnetic Molecularly Imprinted Polymersmentioning
confidence: 99%
“…Molecularly imprinted polymers (MIPs) are obtained from this method and induce highly specific binding sites by template-directed cross-linking of functional monomers. Recently, Wang et al has reported MIT coupled with SPE-HPLC for selective recognition of sesamol . Semiconductive nanocrystal quantum dots (QDs) with high quantum yields, controllable sizes and emission wavelengths, and good chemical stability have been found a wide range of fluorescence sensors.…”
Section: Introductionmentioning
confidence: 99%